WEB-BASED INTERACTIVE HTML LEARNING - Fatkhurrozi, Muhammad Faidhi (IRC, 2015)
Interactive HTML Learning is a web-based system developed to increase the effectiveness of learning HTML language. The web-based system basically is an interactive way of learning through computer browser that will involve two ways communication. This will result of reducing learning curve of users. Through the development of this learning system, more programmers can be made available. The main difference of this system than other than other system is this system will be using the interaction of two ways communication between the user and the system itself. Inputs inserted by the user will have respond from the learning system. The learning system will have attractive interface by including images and colours to avoid text-only learning process. Target user of this interactive HTML learning system is amateur users who has no experience in dealing with programming language. Users now will be able to learn HTML in interactive way and more effective with this system available